HUBUNGAN AKTIVITAS FISIK DENGAN FUNGSI KOGNITIF PADA LANSIA DI DESA PARAN-PADANG KECAMATAN SIPIROK KABUPATEN TAPANULI SELATAN - Fakultas Keperawatan DELI HUSADA Deli Tua (Jurnal Penelitian Keperawatan Medik, 2020)
Elderly is part of the process of growth and development, this is a process that is continuous (continues) naturally. This stage starts from birth and is generally experienced in all living things (Bandiyah, 2009). Cognitive function is the largest part of the brain. Physical activity is identified as one of the factors that are thought to have something to do with cognitive function. The purpose of this study was to determine the relationship between physical activity and cognitive function in the elderly in Paran-padang Village, Sipirok District, South Tapanuli Regency. The research sample was 37 elderly in Paran-padang Village, Sipirok District, Tapanuli Regency. The sampling technique used in this study is probability sampling with the simple random sampling method. This study uses a correlational analytic type with a cross sectional design. The data collection measuring instrument used in this study was a questionnaire sheet. The results of statistical tests with Spearman rho show that there is a relationship between physical activity and cognitive function in the elderly in Paran Padang-Padang Village, Sipirok District, Tapanuli Selatan Regency in 2020 with a P-Value of 0.001 (<0.05). The suggestion is expected that the elderly family should carry out exercise in the elderly more frequently and regularly and also do physical activity.